Functional traits and adaptive capacity of European forests to climate change - Bussotti, Filippo; Pollastrini, Martina; Holland, Vera; Brüggemann, Wolfgang (Environmental and Experimental Botany, 2014)
Increasing temperatures and drought risks through climate change are expected to have several consequences for European forests. Adaptive strategies may include: (i) persistence of the current forest types, thanks to the acclimatization to local conditions and to phenotypic plasticity of the populations; (ii) evolution, or local adaptation, i.e., change in genotype (frequencies) within the same species due to environmental pressure. It is favored by large within population diversity and (when possible) gene flow among populations; (iii) migration and substitution of species; and (iv) extinction of populations with low ecological plasticity, especially at the edges of their distribution or in the case of isolated (relict) populations. Because of the economic and ecological relevance of forests, it is of fundamental importance to apply appropriate forest management to make forests able to cope with the new environmental conditions. This may include changes in the composition and structure of forest stands, selection of adapted provenances of the most important European tree species or, if this is regarded as insufficient, assisted migration (i.e., the use of species suitable for the future climatic conditions) and, alternatively, substitution of native with non native species. The intraspecific (genetic and phenotypic) variability at a given site has been proven to be often higher than the variability among sites. Species with a large distribution range are supposed to have a wide variety of genotypes, allowing them to be adapted to different environmental conditions. Genetic variability and phenotypic plasticity are the key factors for the identification of useful tree genotypes for future forestation programs. Adaptation to drought, i.e., the probably most important future abiotic risk factor for forestry, can be reflected in variation of key functional traits (FT), at morphological, physiological and phenological level. FT utilized to screen for adapted genotypes in common gardens and provenance trials include growth, survival, leaf flushing and senescence, foliar features as leaf mass per area and nitrogen content, water use efficiency (e.g., estimated by analysis of the stable carbon isotopes, d13C) chlorophyll content, photosystem II functioning, and photosynthetic capacity under water shortage. Current modeled simulation of future forest distribution suggests the expansion of forests at the highest latitudes and altitudes, alongside with a reduction in the hottest and driest Mediterranean regions of South Europe. The general expectations, however, may be disproved especially at a regional level, by factors unexpected or not well known, such as possible extreme climatic events and increased roles of parasites/diseases (with negative effects), or high capacity of forest persistence or adaptation (with positive effects). Natural migration and species substitution can be hampered by co-factors of climate change, such as forest fragmentation and increased frequency and intensity of forest fires.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Adaptation; Extinction; functional traits; Local evolution; migration; Phenotypic plasticity; Phenotyping; provenances

Aproximación proteómica para el estudio de la variabilidad genética y la respuesta a estrés en Quercus ilex L. subsp. ballota (Desf.) Samp. - Jorge, I; Navarro Cerrillo, R Mª; Ariza, D; Porras Tejeiro, C J; Jorrín Novo, J V (IV Congreso Forestal Español, 2005)
Our research groups have just initiated a collaborative research project directed to studying variability among populations and responses to stresses in Quercus ilex L . by using a functional genomic approach. Our first experiments intended to analyze the leaf proteome by mean of two- dimensional gel electrophoresis for protein resolution, peptide analysis by mass spectrometry and protein identification by searching in protein or DNA databases. We have used leaves from adult trees and seedlings from different provenances. At the present we are carrying out studies of responses to water stress and pathogens. Results so far obtained and published support proteomics as an useful experimental approach in order to establish and characterize genetic variability among provenances and populations as well as to identify proteins and genes involved in responses to stresses.
Keywords: Drought; proteomic; provenances; Quercus ilex

Phytoclimatic characterization of holm-oak provenances (Quercus ilex L.) in the Central-Northern Iberian Peninsula - Garcia Lopez, J M; Gonzalo Jimenez, J; ALLUÉ CAMACHO, C (Forest Systems, 2002)
This paper presents some contributions to the phytoclimatic characterization of stands of holm-oak (Quercus ilex. L.) in the centre-north of the Iberian Peninsula and the testing of a method of phytoclimatic homologation applicable to the characterization of provenances of the species. For the phytoclimatic characterization, 432 sampling points in the Province of Burgos were considered, corresponding to the centres of cartographic tessellae of actual vegetation in which holm-oak was the principle species of the forest (18,965 ha). The phytoclimatic diagnosis followed the phytoclimatic models of Allué-Andrade. Phytoclimatic territorial models were constructed in digital format on the basis of preliminary territorial factorial estimations, which were used to determine phytoclimatic terns. Based on the establishment of phytoclimatic ambits for the existence of holm-oak stands in Burgos and stratification in accordance with the five phytoclimatic subtypes (VI(IV)1, VI(IV)2, VI(VII), VI(V) and VI), phytoclimatic homologation was performed in three phases of increasing strictness, all based on a comparison of phytoclimatic terns derived from the general and specific phytoclimatic systems. In the strictest homologation, an adequate and territorially compact degree of discrimination was achieved for 2.622.500 ha (Quercus ilex subsp. ballota) and 116.00 ha (Quercus ilex subsp. ilex) in the centre-north of the Iberian Peninsula. The marked edaphic azonality of the species was an important factor in the interpretation of the results.
Keywords: holm-oak; homologation; phytoclimatology; provenances; Quercus ilex L. subsp. ballota (Desf.) Samp.; Quercus ilex L. subsp. ilex

Phytoclimatic characterization of holm-oak provenances (Quercus ilex L.) in the Central-Northern Iberian Peninsula - Garcia Lopez, J. M.; Gonzalo Jimenez, J.; ALLUÉ CAMACHO, C. (Forest Systems, 2002)
This paper presents some contributions to the phytoclimatic characterization of stands of holm-oak (Quercus ilex. L.) in the centre-north of the Iberian Peninsula and the testing of a method of phytoclimatic homologation applicable to the characterization of provenances of the species. For the phytoclimatic characterization, 432 sampling points in the Province of Burgos were considered, corresponding to the centres of cartographic tessellae of actual vegetation in which holm-oak was the principle species of the forest (18,965 ha). The phytoclimatic diagnosis followed the phytoclimatic models of Allué-Andrade. Phytoclimatic territorial models were constructed in digital format on the basis of preliminary territorial factorial estimations, which were used to determine phytoclimatic terns. Based on the establishment of phytoclimatic ambits for the existence of holm-oak stands in Burgos and stratification in accordance with the five phytoclimatic subtypes (VI(IV)1, VI(IV)2, VI(VII), VI(V) and VI), phytoclimatic homologation was performed in three phases of increasing strictness, all based on a comparison of phytoclimatic terns derived from the general and specific phytoclimatic systems. In the strictest homologation, an adequate and territorially compact degree of discrimination was achieved for 2.622.500 ha (Quercus ilex subsp. ballota) and 116.00 ha (Quercus ilex subsp. ilex) in the centre-north of the Iberian Peninsula. The marked edaphic azonality of the species was an important factor in the interpretation of the results.
Keywords: holm-oak; homologation; phytoclimatology; provenances; Quercus ilex L. subsp. ballota (Desf.) Samp.; Quercus ilex L. subsp. ilex

Las técnicas de selección y propagación en la mejora genética del alcornoque - García Valdecantos, J. L. (Scientia gerundensis, 1992)
The role and importance of the techniques of propagation and selection in the cork oak breeding programs are discussed. In the field of propagation, the characteristics of sexuai reproduction are discussed. The author recommends the use of medium or small acorns and empbasizes the need of improving acorn storage procedures. Considering vegetative propagation as the best method to obtain maximal genetic gains, the author emphasizes the difficulties found in the use of cuttings, the fairly good results obtained with grafts, and the promising experiences of tissue culture. The importance of rejuvenating techniques using stump sprouts and suckers for vegetative propagation is strongly emphasized. The selection superior trees for breeding programs in the cork oak is difficult because of the lack of previous experience in genetics of bark production. An experimental method, developed in the province of Cidiz with the help of ICONA, is described. This method is based in an accurate measurement of a number of tree pararneters which are evaluated at the end of a complete harvest cycle (9 years).
Keywords: Cork oak; provenances; seed orchards; tree breeding; vegetative propagation